The Correlation Between TP53 Expression and Ki-67 Proliferation with Bartl Malignancy Degree of Plasma Cell Neoplasm - Isabelle Deli Lestadi; Nurjati Chaerani Siregar; Puspita Eka Wuyung (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Plasma cell neoplasm (PCN) is a neoplastic plasma cell proliferation which includes solitary bone plasmacytoma (SBP), extramedullary plasmacytoma (EMP) and multiple myeloma (MM). Bartl classifies the degrees of PCN as low, intermediate and high. The aim of this study is to find the correlation between tumor suppressor gene p53 (TP53) expression and Ki-67 proliferation with Bartl malignancy degree of PCN. Therefore earlier PCN diagnostic method to prevent the development of PCN into MM can be found.METHODS: Thirty-two PCN cases were classified into three groups based on Bartl’s degrees of malignancy. TP53 and Ki-67 immunohistochemical staining were performed on samples and the percentage of positivity was evaluated.RESULTS: The Bartl’s low degree of malignancy was found in 10 MM cases (31.2%), intermediate degree in 5 SBP cases (15.6%) and high in 2 SBP and EMP cases (6.2%). TP53 expression was obtainable at 4% of low, 16% of intermediate and 10% of high degree. There was a significant difference between TP53 expression in low and intermediate degree (p=0.004). Mean proliferation index of Ki-67 was 57% in low, 44.6% in intermediate, and 32.6% in high degree. There was no significant difference of Ki-67 proliferation indexes among the group (p=0.339).CONCLUSION: Increasing expression TP53 was in accord with Bartl’s degrees of malignancy, especially in low and intermediate degree, but there was no significant difference between Ki-67 proliferation index and Bartl’s degrees of malignancy.KEYWORDS: plasmacytoma, myeloma, TP53, Ki-67, Bartl classification